2012
DOI: 10.2478/v10172-012-0001-z
|View full text |Cite
|
Sign up to set email alerts
|

Co-Mo and Co-Mo-C Alloys Deposited in a Magnetic Field of High Intensity and their Electrocatalytic Properties

Abstract: The article presents results of tests on electrodeposition in a magnetic field of Co-Mo and Co-Mo-C alloys characterised by low overvoltage of hydrogen evolution. Addition of molybdenum and carbon was to lower the values of overvoltage of hydrogen evolution on cobalt. The influence of a magnetic field of high intensity (1 -12 T) on the deposits composition, structure and morphology was determined. The deposition was conducted in a magnetic field of parallel orientation of the magnetic field forces lines in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…[1] The best catalytic properties are found in metals from the platinum group [2][3], but due to their high prices it is impossible to commercialise production of hydrogen as a common energy carrier. A solution to the problem can be application of alloy or composite catalysers of catalytic properties close to those of the platinum metals though much less expensive [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[1] The best catalytic properties are found in metals from the platinum group [2][3], but due to their high prices it is impossible to commercialise production of hydrogen as a common energy carrier. A solution to the problem can be application of alloy or composite catalysers of catalytic properties close to those of the platinum metals though much less expensive [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Current density varied in the range of 7-25 mA/cm 2 at 90-100 °C. The amorphous coatings by the Co-Mo-C alloys were obtained by electrolytic deposition in the magnetic field [25]. The content of molybdenum in the alloys varies from 27.6 to 34.2 аt.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Due to high price of PGMs, a lot of attention is focused on a synthesis of their nanoparticles (Au [2,3], Pt [4]), nanofilms [5][6][7] and alloys [8][9][10][11] that being much cheaper can present close functional properties. It was demonstrated that also alloys of transition metals not containing PGMs, such as: Ni-Mo [12], Co-Mo [13], Co-Mo-C [13], Co-W [14], Co-W-C [14], Zr-Ni-Co [15] can be a very interesting group of materials because of their catalytic properties or ability to absorb hydrogen.…”
Section: Introductionmentioning
confidence: 99%